Living the liquid life: Gender, precarity, and journalism in the post-#metoo era - Melin Margareta; Wiik Jenny (Nordic Journal of Media Studies)
Despite a long-standing trend of increasing women in the profession, masculine norms and gender inequality persist in media work. During the #metoo movement, Swedish journalists launched the #deadline campaign, shedding light on the connection between gender and worsening working conditions. Increasing demands for flexibility have institutionalised temporary contracts, eroded job security, and expanded job precarity, with women and young journalists disproportionately affected. In this article, we explore gendered journalistic precarity and systemic inequalities, challenging the assumption of professional homogeneity in the field of journalism. We conducted 23 interviews with Swedish journalists on temporary contracts, applying a feminist analysis to understand how power dynamics affect their experiences. Five years post #metoo, gender issues have faded from professional discourse. However, the interviews reveal continued gender discrimination and harassment, exacerbated by factors such as age, class, and position in the labour market.